Representational structure of health professionals about care delivery to people living with HIV/Aids - Camila Rodrigues Barbosa; Elizabeth Teixeira; Denize Cristina de Oliveira (Universidad de Antioquia, 2016)
Objective. To analyze the social representation structure of health professionals about care delivery to people living with HIV/AIDS and to reflect on that structure in the light of the National Humanization Policy. Methods. Exploratory study based on the Social Representations Theory, with emphasis on the structural focus. In total, 114 health professionals from Belém, Pará/Brazil participated in the development of the study, working at four services specialized in HIV/AIDS care, between August 2011 and April 2013. The data were collected through free evocations of the inducing term "Taking care of HIV/AIDS patient" and analyzed using the software Ensemble de Programmes Permettant L'analyse des Évocations-EVOC2003. Results. The group of subjects has a positive representation structure, organized around the categories: sensitive care, technical care and educative care. When reflecting on the representations structure, four out of five principles of the National Humanization Policy are observed (principle 1 - valuation of the subjective and social dimensions, principle 2 - stimulus for the production of health and subjects, principle 3 - teamwork and principle 5 - construction of autonomy and empowerment). Conclusion. The social representation structure of the health professionals about care for people living with HIV/AIDS signals the affective, conceptual and informative dimensions, converging with most principles of the Brazilian humanization policy.   How to cite this article: Barbosa CR, Teixeira E, Oliveira DC. Representational structure of health professionals about care delivery to people living with HIV/AIDS. Invest. Educ. Enferm. 2016; 34(3): 528-536.